How Did the Great Recession Affect Different Types of Workers? Evidence from 17 Middle-Income Countries - Cho, Yoonyoung; Newhouse, David (2012)
This paper examines how different types of workers in 17 middle-income countries were affected by labor market retrenchment during the great recession. Impacts on different types of workers varied by country and were only weakly related to the severity of the shock. Among active workers, youth experienced by far the largest adverse impacts on employment, unemployment, and wage employment, particularly relative to older adults. The percentage employment reductions, for example, were greatest for youth in each sector of the economy, as firms reacted to the shock by substituting away from inexperienced workers. Employment rates, as a share of the population, also plummeted for men. Larger drops in male employment were primarily attributable to men's higher initial rate of employment, although men's concentration in the hard-hit industrial sector also played an important role. Within each sector, percentage employment declines were similar for men and women. Added worker effects among women were mild, even among less-educated workers. Differences in labor market outcomes across education groups and urban or rural residence tended to be smaller. These findings bolster the case for targeted support to displaced youth and wage employees. Programs targeted to female and unskilled workers should be undertaken with appropriate caution or empirical support from timely data, as they may not benefit the majority of affected workers.